Pengertian dan Kedudukan Agen dalam Suatu Hubungan Hukum (Analisis dalam Hukum Eropa Kontinental, Anglo Saxon, dan Hukum Islam) - toto tohir (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The word 'agent' is a friendly word for our daily life. Where as, according to the Civil Code Procedure and the Criminal Code Procedure do not the least explain the word 'agent'. It needs to Investigate therefore deeply what Is meant by 'agent' In various kind of law system. It is important to do the Investigation because itwill givejuridical basefor the sides In deciding their right andresponsibility The agent that comes from thelaw concept withthe Anglo Saxon system turned out It can befound In the other law system although their names are different, namely in the Continental Europe and Islam. Agent Is only part of representative with difference in length of their scope. Besides that, the correlation of agence basically rises from negotiation concensually and the agent atau representative is only a mediator. Based on the custom the usage ofword 'agent' so It Is better that Government with House of Representatives compile the completed and comprehensiveActs of Indonesia Agency as soon as possible.